2003
DOI: 10.1088/0031-9155/48/21/005
|View full text |Cite
|
Sign up to set email alerts
|

A novel linear programming approach to fluence map optimization for intensity modulated radiation therapy treatment planning

Abstract: We present a novel linear programming (LP) based approach for efficiently solving the intensity modulated radiation therapy (IMRT) fluence-map optimization (FMO) problem to global optimality. Our model overcomes the apparent limitations of a linear-programming approach by approximating any convex objective function by a piecewise linear convex function. This approach allows us to retain the flexibility offered by general convex objective functions, while allowing us to formulate the FMO problem as a LP problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 47 publications
1
148
0
1
Order By: Relevance
“…Many articles have shown that underdosing even small fractions of the target volume can lead to a drastic reduction of the tumor control probability (see, for example, [9,14,18,24]). Hence, the common practice to prescribe dose to the D 95% , i.e., the dose value at the 95% volume level in the dose volume histogram (DVH), is problematic, unless the dose tail below the D 95% is somehow limited [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many articles have shown that underdosing even small fractions of the target volume can lead to a drastic reduction of the tumor control probability (see, for example, [9,14,18,24]). Hence, the common practice to prescribe dose to the D 95% , i.e., the dose value at the 95% volume level in the dose volume histogram (DVH), is problematic, unless the dose tail below the D 95% is somehow limited [22].…”
Section: Introductionmentioning
confidence: 99%
“…Ehrgott et al (2008) present an extensive survey. When the objective function is linear or can be linearized, the program can be solved with standard commercial software (Lim et al 2007, Romeijn et al 2003, Saka et al 2011, Saka et al 2014. Otherwise, researchers have developed their own the problem-specific algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many mathematical optimization models and algorithms have been proposed for the FMO problem, including linear models [20], mixed integer linear models [11] and nonlinear models [2]. Here, we will use this later approach that penalizes each voxel according to the square difference of the amount of dose received by the voxel and the amount of dose desired/allowed for the voxel.…”
Section: Fmo Modelmentioning
confidence: 99%
“…Here, we will use this later approach that penalizes each voxel according to the square difference of the amount of dose received by the voxel and the amount of dose desired/allowed for the voxel. This formulation yields a quadratic programming problem with only linear non-negativity constraints on the fluence values [20]:…”
Section: Fmo Modelmentioning
confidence: 99%